Natural History of Abortive Medication Withdrawal in the Management of Pediatric Medication Overuse Headache - Pierce, Emily L; Mandel, Alexandra A; Strelzik, Jeffrey A; Langdon, Raquel L; McClintock, William M; Cameron, Mark W; McCracken, Emily E; DiSabella, Marc T (Pain medicine (Malden, Mass.), 2022)
Abstract Objective The objective of this study is to document pain scores during withdrawal of abortive medication in patients diagnosed with medication overuse headache. Design Cross-sectional study. Setting Children’s National Hospital’s Headache Program. Subjects Patients 6–18 years of age who presented to the Headache Clinic at Children’s National Hospital with presumed medication overuse headache between March 2017 and March 2019 were invited to participate. Methods Patients were instructed to abruptly discontinue overused medications and record their headache characteristics daily in a diary for 8 weeks. Results Fourteen diaries were returned and analyzed at a 4-week follow-up visit. Ninety-three percent of the patients were females, with a median age of 14.9 years (standard deviation [SD] = 2.0). The average headache intensity upon study entry was 4.7 out of 10 (SD = 2.5), and the average headache intensity upon study completion was 3.1 (SD = 2.5). Of the patients, 57% had daily headaches upon study entry, 71% had improved pain intensity from the first diary entry to the last diary entry, and 57% had complete headache resolution at an average of 7.6 days from medication discontinuation (SD = 5.1). Ibuprofen was the most overused medication (71%). Conclusions Our findings suggest that medication overuse headache will improve in the majority of pediatric patients who abruptly stop the offending medication(s) in an average of 8 days from withdrawal. Average pain intensity was reduced by more than one point among all patients who stopped taking abortive medications. Further larger-scale studies on medication withdrawal in pediatric patients with medication overuse headache could help us better understand whether this management strategy is effective.